PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NHT TERHADAP KEMAMPUAN BERPIKIR KRITIS IPS KELAS 5 SDN 3 TAMAN AYU TAHUN 2023/2024 - Larasaty, Aulia; Nurhasanah; Novitasari, Setiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the influence of the Numbered Head Together Learning Model on the Critical Thinking Ability of Class V Social Sciences at SDN 3 Taman Ayu. This type of research uses quantitative research with experimental methods. The data collection method is in the form of pretest and posttest test questions. Based on the research results, it was obtained that the t_count ≥ t_table (9,767 ≥ 1,685) and sig.2 tailed ≤ 0.05 (0.001 ≤ 0.05) then the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. The effect size test results obtained were 3,088 in the large category. It can be concluded that there is a significant influence of the Numbered Head Together learning model on the critical thinking abilities of class V students at SDN 3 Taman Ayu with a percentage increase in the results of social studies critical thinking abilities of students who are above the KKM by 70%.